EFFECT OF THYROID HORMONES ON GLUCOSE REGULATION IN PRE AND POST MENOPAUSAL DIABETIC WOMEN - KALASHILPA CHITTIKANNA,; SUMANGALA M. PATIL, (International Journal of Pharma and Bio Sciences, 2017)
There is a mutual influence of thyroid and diabetes and the association between them reported long back. Prevalence of thyroid on diabetics is increasing worldwide. The presence of thyroid usually affects diabetic patients. Aim of the study is to evaluate the relationship between Thyroid hormones and Glucose Regulation in pre and post menopausal diabetic women. Total Sixty women, among them 30 pre menopausal diabetic aged between 25-45 years & 30 Post menopausal diabetic women aged between 46-65 years were selected for the present study. Anthropometric & Physiological parameters were taken. Complete blood count, Fasting blood glucose (FBS), Glycosylated hemoglobin (HbA1C), Thyroid hormone profile (T3, T4, TSH) levels were analyzed. In our study we found, there is significant increase in BSA, BMI, Waist to Hip ratio of Pre menopausal diabetic group compared to post menopausal diabetics where as significant increase in SBP of Post menopausal diabetic group compared to pre menopausal Diabetics & there is non-significant increase in HbA1C levels of post menopause Diabetic group. However, there is non-significant decrease in T3, T4 and significant increase in TSH levels of Pre menopause Diabetic group compared to post menopause diabetics. We found more prevalence of “Hypothyroidism” among pre menopausal diabetic women. So prompt recognition of thyroid dysfunction in premenopausal diabetic women and controlling the blood glucose level is necessary and also routine thyroid screening should be recommended for pre menopausal diabetic and post menopausal diabetic women to detect thyroid abnormalities in most of the patients in subclinical stage.